An Examination of Leader Portrayals in the U.S. Business Press Following the Landmark Scandals of the Early 21st Century - Hannah, David (Journal of business ethics, 2008)
Following the landmark corporate scandals of the early 21st century, there appeared to be a tremendous increase in the U.S. business media’s emphasis on issues of ethics in corporate leadership. The purpose of this research was to examine whether that apparent increase was reflected in an actual change in that media’s portrayals of successful leaders. We content analyzed the text of a total of 180 articles in Business Week, Fortune, and Forbes magazine, 90 from the five years preceding the landmark scandals and 90 from the five years following the scandals. We found no evidence that the landmark scandals had any impact on the media’s incorporation of ethics in their portrayals of leaders. We attribute this substantially to the persistence of a worldview in the U.S. business press that emphasizes leader traits and actions that have a direct impact on corporate profits. Additionally, we found some interesting consistencies and differences in media portrayals across the two time periods, likely related to the rise and fall of dot-com businesses. We discuss the implications of these findings for researchers and corporate leaders.